The Foundation and Work of the Serbian Bookstore in Thessaloniki - Zarković, Vesna S. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
At the end of the 19th century diplomatic activity of the Kingdom of Serbia was reinforced. It had especially come to the fore when in 1886 Stojan Novaković was appointed as the deputy in Constantinople. He, as the experienced diplomat, realized the significance of the national idea spreading, and worked actively to that end. After the signing of consular convention, and opening of Serbian consulates in Osman’s Empire, conditions for the opening of larger number of schools were created for which the permissions from Turkish authorities were to be acquired. As the number of Serbian pupils increased, and the numbers of schools as well, the issue of books supply was raised, which was not easy at all in that time. Turkish government issued the permission in 1890 that books for Serbian schools should be printed in Constantinople. All books which were to be printed had top pass the censorship of the Educational Committee. Thanks to the reinforced Serbian diplomatic activity in spreading the national idea, some shifts were made, which led representatives of Serbs in Osman’s Empire to the idea of opening bookstores. Almost in the same time, bookstores in Prištine, Prizren, and Thessaloniki were opened. The bookstore in Thessaloniki bore the official title the Serbian bookstore, and managed to work and survive despite the propaganda of Bulgarian exarchists which tried to thwart its existence   frequently by associating with Turkish authorities.  The business activity report was filed to the Consulate, which regulated its activities through contracts and measures.
Keywords: Serbian bookstore; Thessaloniki; bookseller; Serbian Consulate; Stojan Novaković; Turkish authorities; Bulgarian agents